A Phase II Trial of a Personalized, Dose-Intense Administration Schedule of 177Lutetium-DOTATATE in Children With Primary Refractory or Relapsed High-Risk Neuroblastoma–LuDO-N - Sundquist, Fredrik; Georgantzi, Kleopatra; Jarvis, Kirsten Brunsvig; Brok, Jesper; Koskenvuo, Minna; Rascon, Jelena; van Noesel, Max; Grybäck, Per; Nilsson, Joachim; Braat, Arthur; Sundin, Mikael; Wessman, Sandra; et al. (Frontiers in Pediatrics, 2022)
Background: Half the children with high-risk neuroblastoma die with widespread metastases. Molecular radiotherapy is an attractive systemic treatment for this relatively radiosensitive tumor. 131I-mIBG is the most widely used form in current use, but is not universally effective. Clinical trials of 177Lutetium DOTATATE have so far had disappointing results, possibly because the administered activity was too low, and the courses were spread over too long a period of time, for a rapidly proliferating tumor. We have devised an alternative administration schedule to overcome these limitations. This involves two high-activity administrations of single agent 177Lu-DOTATATE given two weeks apart, prescribed as a personalized whole body radiation absorbed dose, rather than a fixed administered activity. “A phase II trial of 177Lutetium-DOTATATE in children with primary refractory or relapsed high-risk neuroblastoma - LuDO-N” (EudraCT No: 2020-004445-36, ClinicalTrials.gov Identifier: NCT04903899) evaluates this new dosing schedule. Methods: The LuDO-N trial is a phase II, open label, multi-center, single arm, two stage design clinical trial. Children aged 18 months to 18 years are eligible. The trial is conducted by the Nordic Society for Paediatric Haematology and Oncology (NOPHO) and it has been endorsed by SIOPEN (https://www.siopen.net). The Karolinska University Hospital, is the sponsor of the LuDO-N trial, which is conducted in collaboration with Advanced Accelerator Applications, a Novartis company. All Nordic countries, Lithuania and the Netherlands participate in the trial and the UK has voiced an interest in joining in 2022. Results: The pediatric use of the Investigational Medicinal Product (IMP) 177Lu-DOTATATE, as well as non-IMPs SomaKit TOC® (68Ga-DOTATOC) and LysaKare® amino acid solution for renal protection, have been approved for pediatric use, within the LuDO-N Trial by the European Medicines Agency (EMA). The trial is currently recruiting and it is estimated to be finalized within 3-5 years. Discussion: In this paper we present the protocol of the LuDO-N Trial. The rationale and design of the trial are discussed in relation to other ongoing, or planned trials with similar objectives. Further, we discuss the rapid development of targeted radiopharmaceutical therapy and the future perspectives for developing novel therapies for high-risk neuroblastoma and other pediatric solid tumors.